Enzymatic surface treatment of poly (3‐hydroxybutyrate) (PHB), and poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV). Issue 11 (15th September 2014) - Berezina, Nathalie; Yada, Bopha; Godfroid, Thomas; Senechal, Tangi; Wei, Ren; Zimmermann, Wolfgang
Abstract BACKGROUND Polyhydroxyalkanoates (PHA) are very interesting biopolymers, their most promising applications lie in biomedical science. The wettability of the surface of PHA increases their biocompatibility properties, making them suitable for such applications. RESULTS The treatment of the surface of poly (3‐hydroxybutyrate) (PHB) and poly (3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) films with the cutinase TfCut2 from Thermobifida fusca KW3 resulted in decrease of the water contact angle of PHB films from 90° to 36° and PHBV films from 93–98° to 50–60° with 3‐hydroxyvalerate content ranging from 6 to 9 mol%, respectively. CONCLUSION A linear dependence up to 9 mol% was found between the 3‐hydroxyvalerate content of the PHBV and the resulting water contact angle decrease, caused by partial hydrolysis of the surface of the films by the cutinase. PHBV films with a 3‐hydroxyvalerate content of 6 mol% showed the highest gain in surface hydophilicity following treatment with the enzyme. © 2014 Society of Chemical Industry